Commissioning of the Varian TrueBeam linear accelerator: A multi‐institutional study. Issue 3 (1st March 2013) - Glide‐Hurst, C.; Bellon, M.; Foster, R.; Altunbas, C.; Speiser, M.; Altman, M.; Westerly, D.; Wen, N.; Zhao, B.; Miften, M.; Chetty, I. J.; Solberg, T.
Abstract : Purpose: : Latest generation linear accelerators (linacs), i.e., TrueBeam (Varian Medical Systems, Palo Alto, CA) and its stereotactic counterpart, TrueBeam STx, have several unique features, including high‐dose‐rate flattening‐filter‐free (FFF) photon modes, reengineered electron modes with new scattering foil geometries, updated imaging hardware/software, and a novel control system. An evaluation of five TrueBeam linacs at three different institutions has been performed and this work reports on the commissioning experience. Methods: : Acceptance and commissioning data were analyzed for five TrueBeam linacs equipped with 120 leaf (5 mm width) MLCs at three different institutions. Dosimetric data and mechanical parameters were compared. These included measurements of photon beam profiles (6X, 6XFFF, 10X, 10XFFF, 15X), photon and electron percent depth dose (PDD) curves (6, 9, 12 MeV), relative photon output factors (Scp), electron cone factors, mechanical isocenter accuracy, MLC transmission, and dosimetric leaf gap (DLG). End‐to‐end testing and IMRT commissioning were also conducted. Results: : Gantry/collimator isocentricity measurements were similar (0.27–0.28 mm), with overall couch/gantry/collimator values of 0.46–0.68 mm across the three institutions. Dosimetric data showed good agreement between machines. The average MLC DLGs for 6, 10, and 15 MV photons were 1.33 ± 0.23, 1.57 ± 0.24, and 1.61 ± 0.26 mm, respectively. 6XFFF and 10XFFF modes had average DLGs of 1.16 ± 0.22 and 1.44 ± 0.30 mm, respectively. MLC transmission showed minimal variation across the three institutions, with the standard deviation <0.2% for all linacs. Photon and electron PDDs were comparable for all energies. 6, 10, and 15 MV photon beam quality, %dd(10)x varied less than 0.3% for all linacs. Output factors (Scp) and electron cone factors agreed within 0.27%, on average; largest variations were observed for small field sizes (1.2% coefficient of variation, 10 MV, 2 × 2 cm 2 ) and small cone sizes (<1% coefficient of variation, 6 × 6 cm 2 cone), respectively. Conclusions: : Overall, excellent agreement was observed in TrueBeam commissioning data. This set of multi‐institutional data can provide comparison data to others embarking on TrueBeam commissioning, ultimately improving the safety and quality of beam commissioning.